Chromosome-Level Assembly of Male Opsariichthys bidens Genome Provides Insights into the Regulation of the GnRH Signaling Pathway and Genome Evolution - Dong Liu; Lang Gui; Yefei Zhu; Cong Xu; Wenzong Zhou; Mingyou Li (Biology, 2022)
The hook snout carp Opsariichthys bidens is an important farmed fish in East Asia that shows sexual dimorphism in growth, with males growing faster and larger than females. To understand these complex traits and improve molecular breeding, chromosome-level genome assembly of male O. bidens was performed using Illumina, Nanopore, and Hi-C sequencing. The 992.9 Mb genome sequences with a contig N50 of 5.2 Mb were anchored to 38 chromosomes corresponding to male karyotypes. Of 30,922 functionally annotated genes, 97.5% of BUSCO genes were completely detected. Genome evolution analysis showed that the expanded and contracted gene families in the male O. bidens genome were enriched in 76 KEGG pathways, and 78 expanded genes were involved in the GnRH signaling pathway that regulates the synthesis and secretion of luteinizing hormone and glycoprotein hormones, further acting on male growth by inducing growth hormone. Compared to the released female O. bidens genome, the number of annotated genes in males was much higher (23,992). The male chromosome LG06 exhibited over 97% identity with the female GH14/GH38. Male-specific genes were identified for LG06, where structural variation, including deletions and insertions, occurred at a lower rate, suggesting a centric fusion of acrocentric chromosomes GH14 and GH38. The genome-synteny analysis uncovered significant inter-chromosome conservation between male O. bidens and grass carp, the former originating from ancestral chromosome breakage to increase the chromosome number. Our results provide a valuable genetic resource for studying the regulation of sexual dimorphism, sex-determining mechanisms, and molecular-guided breeding of O. bidens.